The relationship between quality dimensions, tourist satisfaction and behavioral intentions in Malaysian food context: moderating role of destination image - Nezakati, Hossein *; Yuhanis, Abdul Aziz; Dahlia, Zawawi (2015)
The purpose of this study is to develop an integrated model that examines the relationship of three elements of quality dimensions (food, service, and physical environment) and tourist food satisfaction and behavioral intentions in Malaysian context with considering the moderating role of destination image in the relationship between tourist food satisfaction and behavioral intentions. Data were collected from international tourists who visited Kuala Lumpur and Selangor tourist attraction areas via a self-administered questionnaire. Structural Equation Modeling shows that quality of food, service, and physical environment were all important determinants of tourist food satisfaction. In addition, this study revealed that, destination image cannot significantly moderate the relationship between tourist food satisfaction and behavioral intentions. Finally, the result revealed that tourist satisfaction is a strong predictor of behavioral intentions. The study findings and the proposed model will help researchers learn more about the link between quality of food, service, and physical environment, tourist satisfaction toward Malaysian food and their behavioral intentions. The findings may provide guidance to restaurant managers to deliver high service quality to increase tourists' food satisfaction and behavioral intentions.